2013
DOI: 10.1007/s00210-013-0891-y
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-induced desensitization of human β3-adrenoceptors expressed in human embryonic kidney cells

Abstract: β3-Adrenoceptors are resistant to agonist-induced desensitization in some cell types but susceptible in others including transfected human embryonic kidney (HEK) cells. Therefore, we have studied cellular and molecular changes involved in agonist-induced β3-adrenoceptor desensitization in HEK cells. Cells were treated with isoprenaline or forskolin, and following wash-out, cyclic adenosine monophosphate (cAMP) accumulation in response to freshly added agonist was quantified. Receptor and G protein expression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
32
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 46 publications
6
32
0
1
Order By: Relevance
“…Accordingly, studies with b 3 -adrenoceptors transfected into Chinese hamster ovary cells reported a lack of desensitization with agonist exposure of up to 1 hour (Chaudhry and Granneman, 1994), whereas longer exposure (6-24 hours) resulted in desensitization (Chambers et al, 1994;Candelore et al, 1996); however, the latter occurred in the absence of receptor downregulation and was rather explained by a reduced G s expression (Chambers et al, 1994). On the other hand, b 3 -adrenoceptor desensitization and downregulation can occur when transfected into other cell types such as human embryonic kidney cells (Chaudhry and Granneman, 1994;Michel-Reher and Michel, 2013). Studies with natively expressed b 3 -adrenoceptors have yielded both negative (Carpene et al, 1993;Curran and Fishman, 1996) and positive findings (Granneman and Lahners, 1992;Bengtsson et al, 1996;Scarpace et al, 1999;Hutchinson et al, 2000), which is in sharp contrast to the desensitization of b 1 -and b 2 -adrenoceptors observed in almost every cell type ever studied.…”
Section: Unique Regulation Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, studies with b 3 -adrenoceptors transfected into Chinese hamster ovary cells reported a lack of desensitization with agonist exposure of up to 1 hour (Chaudhry and Granneman, 1994), whereas longer exposure (6-24 hours) resulted in desensitization (Chambers et al, 1994;Candelore et al, 1996); however, the latter occurred in the absence of receptor downregulation and was rather explained by a reduced G s expression (Chambers et al, 1994). On the other hand, b 3 -adrenoceptor desensitization and downregulation can occur when transfected into other cell types such as human embryonic kidney cells (Chaudhry and Granneman, 1994;Michel-Reher and Michel, 2013). Studies with natively expressed b 3 -adrenoceptors have yielded both negative (Carpene et al, 1993;Curran and Fishman, 1996) and positive findings (Granneman and Lahners, 1992;Bengtsson et al, 1996;Scarpace et al, 1999;Hutchinson et al, 2000), which is in sharp contrast to the desensitization of b 1 -and b 2 -adrenoceptors observed in almost every cell type ever studied.…”
Section: Unique Regulation Profilementioning
confidence: 99%
“…Studies with natively expressed b 3 -adrenoceptors have yielded both negative (Carpene et al, 1993;Curran and Fishman, 1996) and positive findings (Granneman and Lahners, 1992;Bengtsson et al, 1996;Scarpace et al, 1999;Hutchinson et al, 2000), which is in sharp contrast to the desensitization of b 1 -and b 2 -adrenoceptors observed in almost every cell type ever studied. Interestingly, in cases where b 3 -adrenoceptor desensitization was observed, it often occurred at the level of receptor mRNA expression (Granneman and Lahners, 1992;Bengtsson et al, 1996;Scarpace et al, 1999) or that of signaling molecules activated by the receptor (Chambers et al, 1994;Michel-Reher and Michel, 2013), whereas downregulation of the receptor itself at the protein level has rarely been reported . The Trp64Arg polymorphism of the receptor apparently affects neither the lack of downregulation in Chinese hamster ovary cells (Candelore et al, 1996) nor the desensitization in human embryonic kidney cells (Vrydag et al, 2009).…”
Section: Unique Regulation Profilementioning
confidence: 99%
“…In this respect, demonstrating this novel role of β 3 -AR in renal physiology is particularly intriguing in light of potential therapeutic applications of β 3 -AR–acting drugs in diseases characterized by altered diuresis. Moreover, β 3 -AR is relatively resistant to agonist-induced desensitization, 19 which would ensure prolonged pharmacologic stimulation in vivo . In addition, due to the limited number of tissues expressing β 3 -AR, compared with β 1-2 -AR, β 3 -AR agonists are supposed to show a low systemic off-target effect 14 …”
mentioning
confidence: 99%
“…
Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is frequently used as loading control in immunoblot experiments (Hsu et al 2014;Oldenburger et al 2014;Wang et al 2014).We have recently reported a study on the homologous desensitization of human β 3 -adrenoceptors stably expressed in human embryonic kidney cells (Michel-Reher and Michel 2013). As part of that study, we have used immunoblots to determine the effect of treatment with the β-adrenoceptor agonist isoprenaline (10 μM for 24 h) on the abundance of several G-protein α-subunits at the protein level.
…”
mentioning
confidence: 99%